Dynamic capabilities and high-tech entrepreneurial ventures' performance in the aftermath of an environmental jolt. Issue 3 (June 2021) - Colombo, Massimo G.; Piva, Evila; Quas, Anita; Rossi-Lamastra, Cristina
Abstract: This paper contributes to studies on dynamic capabilities (DCs) by showing that a neglected environmental contingency – i.e. the occurrence of a jolt – shapes the DCs–performance relationship. We focus on high-tech entrepreneurial ventures because these are the firms that jolts affect most; in so doing, we also advance the understanding of DCs in the entrepreneurship field. We argue that, in the aftermath of an environmental jolt, the high-tech entrepreneurial ventures that use internationalization and new product development capabilities to modify their resource configuration and regain environmental fit enjoy better performance. Econometric estimates on a sample of 340 Italian high-tech entrepreneurial ventures confronting the consequences of the global economic crisis that began in 2008 confirm that separately using these two DCs has a positive performance effect. This effect is stronger for relatively smaller ventures. Interestingly, despite synergies should arise from the combined use of the two DCs, we do not detect any superadditive effects.